Identification, distribution, and adult phenology of the carrion beetles (Coleoptera: Silphidae) of Texas - Mullins, Patricia L.; Riley, Edward G.; Oswald, John D. (Zootaxa, 2013)
The carrion beetles (Coleoptera: Silphidae) of Texas are surveyed. Thirteen of the 14 species, and five of the six genera, of this ecologically and forensically important group of scavengers that have previously been reported from Texas are confirmed here based on a study of 3,732 adult specimens. The one reported, but unconfirmed, species, Oxelytrum discicolle, was probably based on erroneous label data and is excluded from the Texas fauna. Two additional species, Nicrophorus sayi and N. investigator are discussed as possible, but unconfirmed, components of the fauna. Taxonomic diagnoses, Texas distribution range maps, seasonality profiles, and biological notes are presented for each confirmed species. The confirmed Texas silphid fauna of 13 species comprises 43% of the 30 species of this family that are known from America north of Mexico. The highest richness (11 species) is found in the combined Austroriparian and Texan biotic provinces of eastern Texas. Phenologically, three species (Necrophila americana, O. rugulosum and Nicrophorus tomentosus) exhibit bimodal adult temporal occurrence patterns with peaks in the spring and late summer or fall; four species (Oiceoptoma noveboracense, Necrodes surinamensis, Nicrophorus carolinus, and N. orbicollis) exhibit unimodal occurrence patterns with a single peak in late spring or early summer; one species (Oiceoptoma inaequale) exhibits a unimodal occurrence pattern with a single peak in early spring; and five species (Thanatophilus truncatus, Nicrophorus americanus, N. marginatus, N. mexicanus and N. pustulatus) display unimodal occurrence patterns with peaks in late summer or early fall.